Role of Oral Medium Chain Triglyceride Oil in Low Birth Weight Neonates: A Randomized Controlled Trial - Hameed, Rida; Asif, Aqsa Arooj (Indus Journal of Bioscience Research, 2025)
Introduction: Low birth weight neonates are at increased risk of poor neurodevelopmental outcomes. Head circumference is an important anthropometric measure that correlates with brain growth and neurodevelopment. Medium chain triglycerides (MCT) oil provides readily available energy and may support growth in preterm and low birth weight infants. Methodology: This randomized controlled trial was conducted at the Department of Pediatrics, Sharif Medical City Hospital, Lahore, from August 7, 2024 to February 6, 2025. A total of 460 low birth weight neonates (birth weight <2.5 kg) aged 1-28 days were randomly assigned to receive either breast milk with MCT oil or breast milk alone. Occipitofrontal circumference (OFC) was measured at baseline and after 4 weeks of intervention. The primary outcome was mean increase in OFC. Results: Both groups had comparable baseline characteristics. The mean increase in OFC was 1.58±0.19 cm in the MCT oil group compared to 0.97±0.66 cm in the control group (p=0.001) after 4 weeks of intervention. Conclusion: Medium chain triglycerides oil supplementation significantly improved head circumference growth in low birth weight neonates compared to the control group. This substantial difference suggests MCT oil effectively enhances brain growth in this vulnerable population. We recommend considering MCT oil supplementation as a nutritional intervention in clinical practice for optimizing developmental outcomes in low birth weight infants.